Sustainable energy policies for Europe : towards 100% renewable energy - Hinrichs-Rahlwes, Rainer; Lins, Christine; Geiss, Jan; Kahles, Markus; Müller, Thorsten (CRC Press/Balkema, 2013)
"The discussion about energy perspectives beyond 2020, up to 2030 and eventually 2050, has started. There seems to be a verbal consensus about the necessity of ambitious climate change mitigation policies, without a convincing perspective of the necessary policy decisions to be achieved in due time. Solutions for greenhouse gas reduction as well as for energy security vary from aiming at 100% renewable energies and setting up appropriate policy frameworks to a mix of renewables with so-called clean fossil and nuclear energy. This book provides an analysis of the different approaches and the reasons why there is no sustainable alternative to aiming at 100% renewables -- and how this vision could come true. The book provides an overview and in-depth analysis of a vital debate. It describes how the present policy framework with 2020-targets for the share of renewables, for increase of energy efficiency and for greenhouse gas emissions reduction was developed and how it was implemented so far. Further, it describes and analyses the emerging debate about the future of our energy system, and about necessary next steps and targets towards 2030"-- Provided by publisher.
"A Balkema book."
Keywords: Energy policy -- Europe.; Renewable energy sources -- Government policy -- Europe.; Europe.; elektronické knihy; electronic books